The drama of Ephesians : participating in the triumph of God - Gombis, Timothy G., 1972- (Downers Grove, Ill. : IVP Academic, 2010)
Timothy Gombis has rediscovered Ephesians as a deeply dramatic text that follows the narrative arc of the triumph of God in Christ. Here Paul invites the church to celebrate and participate in this divine victory over the powers of this present age. In Gombis's dramatic reading of Ephesians we are drawn into a theological and cultural engagement with this epochal story of redemption.--From publisher description
Exploring the drama of Ephesians -- Some mysterious actors on the stage -- Transforming the imagination -- God's victory over the powers -- Embodying God's victory as an apostle -- Empowering subversive performances -- Performing the divine warrior -- Conclusion : the drama of Ephesians : Christ, the powers and the subversive people of God.
Includes bibliographical references (p. [185]-186) and index.
Keywords: Bible. -- Criticism, interpretation, etc; Drama -- Religious aspects -- Christianity